Prices and Unit Values in Poverty Measurement and Tax Reform Analysis - Gibson, John; Rozelle, Scott (Published by Oxford University Press on behalf of the World Bank, 2014)
Researchers often use unit values (household expenditures on a commodity divided by the quantity purchased) as proxies for market prices when calculating poverty lines and estimating consumer demand equations. Such proxies are often needed because community price surveys in developing economies are either absent or suffer quality problems. However, using unit values may result in biases due to measurement error and quality effects. In a household survey experiment, information on prices was obtained in three ways: from unit values, from a market price survey, and from the opinions of householders who were shown pictures of items and asked to report the local price. The three sets of price data are used to calculate poverty lines, estimate price elasticities, and analyze marginal tax reforms. There are substantial biases when unit values are used as a proxy for market price, even when sophisticated correction methods are applied. Performance was better for the price opinions of household members. The results highlight the importance of price collection methods and the need to consider the wider costs of having potentially unreliable community-level price data.